2019
DOI: 10.2147/cmar.s206817
|View full text |Cite
|
Sign up to set email alerts
|

<p>Frequency of germline mutations in BRCA1 and BRCA2 in ovarian cancer patients and their effect on treatment outcome</p>

Abstract: Aim of work Reporting the incidence and the variants of BRCA1 /2 mutations in ovarian cancer patients exploring their effects on the treatment outcomes. Patients and methods In total, 104 patients with epithelial ovarian cancer were prospectively recruited to the study. Analysis consisted of the sequencing of all the translated exons and immediately adjacent intronic regions of the BRCA1/2 genes. Responses to multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In general, the BRCA1/2 mutation frequencies in Asian countries seems to be higher than that in Western countries. The deleterious germline BRCA1/2 mutant rate in our study was similar to some of the above work (13,16). In addition, we identified 4.3% germline BRCA1 mutation as LGRs, which suggests LGRs detection should be considered in mutation screening and genetic counseling in HGSOC patients, especially for young patients without SNV and indel.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In general, the BRCA1/2 mutation frequencies in Asian countries seems to be higher than that in Western countries. The deleterious germline BRCA1/2 mutant rate in our study was similar to some of the above work (13,16). In addition, we identified 4.3% germline BRCA1 mutation as LGRs, which suggests LGRs detection should be considered in mutation screening and genetic counseling in HGSOC patients, especially for young patients without SNV and indel.…”
Section: Discussionsupporting
confidence: 88%
“…One study on germline BRCA1/2 mutation in 1915 unselected ovarian carcinomas was conducted in the United States, they found the deleterious mutation frequency including SNV, indel and LGRs in 1498 HGSOC patients was 16.0% by targeted capture (11), while another study from the United States showed that 98 out of 433 (22.6%) HGSOC patients were identified with germline BRCA1/2 mutation (SNV, indel and LGRs) by sequencing and MLPA (12). In a prospectively study mainly focused on the Arab population, a prevalence of 25.7% deleterious germline BRCA1/2 mutation (SNV and indel) was found in 74 HGSOC patients by sequencing (13). Among Asian countries, a relatively small number screening LGRs) and the result was consistent with a respective study in Japan that reported 28.5% of germline BRCA1/2 mutation (SNV and indel) by NGS testing (14,15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients' age, tumor stage, and histological subtype are the most important prognostic factors 29 . Based on 104 patients with epithelial ovarian cancer, Ashour et al showed that 86.4% of patients harboring BRCA1/2 mutations were younger than 50 years old, suggesting that the age at diagnosis was a strong predictor of the presence of pathogenic BRCA1/2 mutations 30 . In another study of stage II-IV high-grade epithelial ovarian cancer, deleterious germline BRCA mutations were detected and patients' mean age at diagnosis was younger for patients harboring BRCA1 mutations than patients harboring BRCA2 mutations (52 years vs. 57 years, respectively, P = 0.06) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, overall, BRCA2 mutations appear to be more common than BRCA1 mutations in the East Asian population in contrast to white populations, in which BRCA1 mutations may be as common as or more frequent than BRCA2 mutations [24]. To refine BC risk stratification, it is essential to validate these single nucleotide polymorphisms (SNPs) in specific ethnic groups before assessing the polygenic risk scores [25].…”
Section: Introductionmentioning
confidence: 99%